Glomalin and carbon levels as a function of soil aggregates in ecosystems and agroecosystems in the Peruvian Amazon (Bioagro, 2024)
The Amazon rainforest of Peru has experienced major changes in land use, where the forest ecosystem undergo deforestation for the installation of silvopastures and agricultural crops such as coffee and cocoa, which has contributed to the increase of CO2 in the atmosphere. This study evaluated glomalin and carbon levels based on soil aggregates in three types of systems (environments): i) forest ecosystem, ii) silvopasture agroecosystem, and iii) coffee agroecosystem. In each of them, nine plots of 100 m2 were established and soil samples were extracted at a depth of 0-20 cm. Soil organic carbon (SOC), extractable glomalin (EG) and total glomalin (TG) were evaluated in four different ranges of soil aggregate sizes (>2 mm, 2-1 mm, 1-0.25 mm, and 0.25 mm). The effect of the three environments and soil aggregates on SOC and glomalin was analyzed using ANOVA, and a test of regression. The ecosystem type significantly influenced the availability of SOC and glomalin; the highest SOC was obtained in the coffee plantations, followed by the forest with 101.08 and 80.17 t·ha-1. The forest presented a higher concentration of EG and TG compared to the coffee plantation and silvopastures. The aggregate sizes significantly influenced the availability of SOC, EG and TG; as they were smaller the SOC and glomalin content decreased. The ecosystem type and soil aggregates significantly influenced the availability of SOC and glomalin in the three studied environments.
Keywords: Coffee; deforestation; forest; glomalina; silvopasture